2009
DOI: 10.1007/s10529-009-9932-5
|View full text |Cite
|
Sign up to set email alerts
|

Acyl migration during deacylation of phospholipids rich in docosahexaenoic acid (DHA): an enzymatic approach for evidence and study

Abstract: Non-enzymatic acyl migration could be counter-productive for the preparation of structured phospholipids with docosahexaenoic acid (DHA) at a designated position. Therefore enzymatic approaches have been developed to investigate acyl migration. First, acyl migration from sn-2 to sn-1 position has been set into relief by a three step enzymatic method using a typo-selective lipase, a phospholipase A2 and a non-selective lipase. The effect of reaction temperature on acyl migration from sn-2 to sn-1 was monitored:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
2
9
0
1
Order By: Relevance
“…4, which also indicated that the extent of acyl migration from sn ‐2 to sn ‐1 on LPC was facilitated by the higher temperature. These results were consistent with previous reports 23, 24.…”
Section: Resultssupporting
confidence: 94%
“…4, which also indicated that the extent of acyl migration from sn ‐2 to sn ‐1 on LPC was facilitated by the higher temperature. These results were consistent with previous reports 23, 24.…”
Section: Resultssupporting
confidence: 94%
“…Such rearrangement leads to six different lyso PCs consisting of three enantiomeric pairs of positional isomers. This phenomenon was observed by many authors (Adlercreutz & Wehtje, 2001;Poisson, Devos, Godet, Ergan, & Pencreac'h, 2009;Vikbjerg, Mu, & Xu, 2007). In methodology concerning positional analysis of PC, only acyl migration constitutes a serious drawback, which could lead to incorrect final results.…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, 2-LPLs are thermodynamically more stable than 1-LPLs and intramolecular acyl migration from the sn2 to the sn1 position was shown to readily occur (Plückthun and Dennis, 1982). In our case, a multi-step enzymatic method was developed to address this issue (Poisson et al, 2009). The LPLs produced by the selective hydrolysis of I. galbana phospholipids with Lipase F AP-15 ® were further hydrolyzed using a phospholipase A2.…”
Section: Lipase-catalyzed Deacylation Of Phospholipidsmentioning
confidence: 94%